(untitled) (Kairaranga, 2004)
This research article summaries a study that set out to collect information about the actions that three primary schools have taken to develop a more positive school culture. The aim was to identify in what ways a change in culture could contribute to an improvement in school relationships and a reduction in bullying. The research questions focused on what the schools were like previously, how change was initiated, what programmes and community support were used, what the outcomes have been for adults and students, and what were the current challenges and goals that each school faced. A researcher was assigned to each school where they undertook interviews with a range of adults in the school and facilitated focus groups with students. The results of the comparative analysis show that there are identifiable factors common to the approaches used by all three schools. These factors were the importance of leadership, the centrality of relationships, the nature of the programmes adopted, and finally, the nature of the change process itself. While there were many differences between the schools, these differences did not alter the relevance of the factors identified above.